Evaluasi Implementasi Program Badan Usaha Milik Desa (BUMDes) Sendang Pinilih di Desa Sendang, Kecamatan Wonogiri, Kabupaten Wonogiri - Ike Putri Wulansari; Wahyu Nurharjadmo (Jurnal Mahasiswa Wacana Publik, 2021)
This research was conducted at BUMDes Sendang Pinilih, Wonogiri Regency. This study aims to evaluate the implementation of Sendang Pinilih BUMDes Program and find out what factors influence it. This research is qualitative descriptive study. Data obtained through interviews, documentation, and observations were analyzed using analysis model Miles and Huberman. The results showed that the implementation of the program was divided into three stages, organization, interpretation, and application. At the organizing stage it was not completely appropiate, because not all business units written in the rules were implemented. In the interpretation, there are still managers and members who have concurrent duties, the service period of one management period does not match the AD/ART with the Decree, and there are differences in writing of the distribution business results. At the implementation stage, in carrying out the work program, it has been running in accordance with the duties and regulations, but collaboration with BUMDes Rahayu is not through a collaboration script. As for the implementation of work plans business unit development supervision, reports from the operational executive board, and accountability have been carried out in accordance with written regulations. The driving factors for the implementation, include policy standards and objectives, policy sources, interorganizational communication and implementation activities, characteristics of the implementing agency, economic and social conditions, while the inhibiting factors are the political condition and attitude of the implementers.